Intelligent control of a modular power assisted stretcher for indoor application - T. Dechathanat (2020)
© Published under licence by IOP Publishing Ltd. This paper presents the development of an intelligent control of a modular power assisted stretcher movement on flat and sloped floors for indoor environment. Conceptual design techniques are used to select the best concept for prototyping power assist systems. The operator's movement intention and related voltage data is sensed by an Eight-axis hall effect sensor. It proposes the use of PID controller to optimize and maintain the velocity of the stretcher adapted to different weight and floor conditions. A stepping motor is applied to drive each wheel to respond appropriately to different floor and steering conditions (flat or sloped, straight section or turns). Without assistance it would be impractical for an operator to move a loaded stretcher (with patient and accessories) weighing up to approximately 100 kg on 15 degrees straight slope-up/slope-down floor sections. The power assist application turns this into an easy operation.